Associations Between Asthma and Polycystic Ovary Syndrome: Current Perspectives - Xu, Yue; Zhou, Zhi-Yang; Pan, Jie-Xue; Huang, He-Feng (Frontiers in Endocrinology, 2022)
A potential correlation between polycystic ovary syndrome (PCOS) and asthma, used to be identified as diseases originating from two independent systems, has been supported by increasing evidence. From an epidemiological perspective, mounting studies have confirmed that women suffering from PCOS exhibit increased susceptibility to asthma. Meanwhile, PCOS and asthma seem to share several mutual pathological changes, such as metabolic syndrome, impaired fertility, irregular menstruation, systemic inflammation, etc. Here, we further elucidate the correlation between asthma and PCOS by focusing on the internal common pathophysiology and adverse influences on women’s health. Understanding the internal connection between PCOS and asthma may shed light on developing new prevention and control strategies to fight against these conditions.